Plataforma online para edición de video enfocado en contenido de negocio y emprendimiento en el Perú - Chavez Del Arca, Javier Isauro (2024)
EditaYa is an online editing platform focused on entrepreneurship issues that helps make quick edits through video templates and organize future work through a calendar that seeks to improve times when creating this type of content.